Quality Function Deployment in Healthcare: Systematic Literature Review - Sukma, Dias Irawati; Setiawan, Indra; Kurnia, Hibarkah; Atikno, Welly; Purba, Humiras Hardi (Jurnal Sistem Teknik Industri, 2022)
More specific knowledge about Quality Function Deployment (QFD) has grown rapidly. There is a lot of research on the application of QFD in various industrial sectors including manufacturing, construction and services. However, it is still found at least the implementation of QFD in health services. This paper aims to provide a broad understanding and knowledge of the application of QFD in the healthcare industry. This paper also informs that QFD is a method that is not yet popular to be applied in the service industry, including health services. The approach used is Systematic Literature Review. This paper involves a review study of various papers from well-known databases related to the implementation of QFD in the healthcare industry. The results showed that QFD can improve service and create customer satisfaction. QFD is a tool that can be used to assist companies in improving services by translating consumer desires into the company's technical characteristics. QFD applications are also often integrated with other approaches so that QFD can be said as a complementary method that is able to provide maximum results. This paper provides benefits for practitioners to increase knowledge and references to improve company performance related to QFD applications in health services.